Servicio de asesoría contable-tributaria para los socios del centro agrícola cantonal de Quevedo, año 2014 - Quinteros Campos, Ximena Nathaly (2015)
The currently implemented in the country system is based on tax returns, in which agriculture is immersed and with little knowledge for that reason this research entitled "Service-tax accounting advice for members of the Centre Agricultural Cantonal de Quevedo (CACQ), 2014 "projecting advice to farmers establishing overall objective is to implement services accounting and tax advice to partners CACQ and as specific objeticos, a diagnosis of the current situation of equity- area tributary of CACQ, identify deficiencies partners Quevedo Cantonal Agricultural Center in accounting and taxation for the management of their business issues and formulate a proposal for care-tax accounting for members of Cantonal Agricultural Center Quevedo advice. The methods used in the research are inductive, deductive, analytic and synthetic with a type of descriptive research - explanatory meetings structuring in the 124 partners, interview with the president of CACQ and using primary and secondary information to reach the research results , identifying which of the partners 82% do not keep records of income and expenses of their business, 70% do not know which is the singable advice - Tax, he 48 has not requested any advisory service, partners consider important when contracting the service tax for accounting advice, reliability (28%), final results (24%) and cost of service (48%), 81% are enrolled in the SRI, 66% meet tax obligations, 97% believe it is necessary that there trainings for tax matters, in 100% of surveys and interviews consider it necessary to implement a Care Facility Advisory Service Accounting-Tax for Members of the Cantonal Agricultural Center Quevedo.